An exploration of children's drawing, talking and thinking - Gamble, Marjolein (School of Education, 2023)
This study explores children's ways of conceptualisation through what children draw and what they say about their drawings. Drawings taken from 40 children between the ages of 5-10 form the main data of the study. Ten basic categories are drawn from a careful analysis of the drawings. The study also includes what children say about their drawings. The talk about their own drawings forms the language component of the study. The talk is organised into eight basic language categories drawn from an analysis of the talking data. Piaget's theoretical understanding of children's cognitive development is used to frame the data. Lowenfeld's (1975) broad developmental stages of children's art was used to test for correlation with the sample's output. In addition, Sinclair's (1992) linking of children's first utterances with the form of children's most fundamental self-expressions in language, are annotated. Piaget's cognitive understanding of children's developmental thinking strategies are used to explain the strategies children use in their drawings. Indications are that the drawings do reflect a developmental process, but this needs to be borne out by further research. The study bears out Lowenfeld's (1975) contention that there are unique ways of applying the basic conceptualisations of spatial relations in children's drawings. The presence of first and second language speakers in the sample points to the possibility that second language users may resort to basic and fundamental language structures when they use a second language. This aspect too would need more specific further research. Finally, the categories found could form a tool to enlarge an understanding of the found trends with a larger sample. The objective of obtaining some understanding of how children's minds work in the way they solve and approach their drawing and talking tasks was achieved within the constraints of a relatively small sample of children.